Factores asociados a la infección por covid-19 en personas previamente vacunadas en Loreto 2021-2022 - Hidalgo Amasifuen, Christian (2023)
Objective: To evaluate the factors associated with COVID-19 infection in previously vaccinated persons in Loreto 2021-2022. Methods: Observational, cross-sectional, descriptive and retrospective study. The database of previously vaccinated patients from the "Notiweb de la Dirección de Epidemiología de la Geresa Loreto" of COVID-19 from 2021 and 2022 was analyzed. Data privacy was respected through anonymity. Data analysis was performed by SPSS v26. Results: 21 497 data from persons vaccinated between 2021 and 2022 were analyzed. Factors associated with COVID-19 infection in previously vaccinated persons were age 30-59 years (60.8%), female sex (58.4%), rural area districts (35.7%), self-employed (55.5%), non-health care workers (79, 3%), no comorbidities (73.1%), did not require hospitalization (87.4%), no reinfection (76.8%), moderate COVID (58.5%) and molecular confirmatory test (50.8%), having received only 2 doses (96.3%) and 3 doses (60,5%). However, the lowest proportion occurred in those who have received all 4 doses (4.2%).